STRATEGI BERTAHAN HIDUP (LIFE SURVIVAL STRATEGY) BURUH TANI DI DESA TOMBATU DUA UTARA KECAMATAN TOMBATU UTARA - Finna Kumesan; Charles R. Ngangi; Melissa L.G. Tarore; Paulus A. Pangemanan (COCOS, 2015)
ABSTRACT This study aimed to describe a survival strategy Peasants in theVillage of North Tombatu Two District North Tombatu. The research was conducted during the five months from January to May 2015 in the Village of North Tombatu Two District North Tombatu. The data used in- clude the primary and secondary data. Primary data collection using a list of questions prepared in the form of the questionnaire, while secondary data taken from the agencies - agencies in- volved in this research that North Tombatu Two Village Office. Sampling that all members of the population of Peasants. Samples were taken for one week a total of 32 heads of families. The analytical method used is Descriptive Analysis.The results showed that with low income farm workers they can still survive. By working odd jobs to supplement their income farm workers even though only enough to meet basic needs. The most dominant strategies used by farm work- ers is Controlling Food Consumption and spending that is by utilizing all available resources to suppress expenditure. Farm workers often received help from neighbors or nearby relatives, be- sides the majority of farm workers received help from the government, so it helps in meeting dai- ly needs - today and for membiyayai child's school. The participation of farmers in gathering al- so help farmers to cope with a sudden need and to build a house. Â Keyword : Life Survival, hodge, life necessities